2010
DOI: 10.1002/cncr.25046
|View full text |Cite
|
Sign up to set email alerts
|

Can we better select patients with metastatic renal cell carcinoma for cytoreductive nephrectomy?

Abstract: BACKGROUND:The benefits of cytoreductive nephrectomy (CN) in metastatic renal cell carcinoma (mRCC) should outweigh surgical morbidity. Even when the generally agreed upon selection criteria for CN are met, some patients do poorly after surgery. The objective of this study was to identify preoperative factors that were prognostic of outcome in patients who were being considered for CN. METHODS: The authors conducted a retrospective study to investigate the overall survival (OS) of patients who underwent CN usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
117
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 195 publications
(129 citation statements)
references
References 48 publications
8
117
0
4
Order By: Relevance
“…Patients most likely to benefit from cytoreductive nephrectomy before systemic therapy are those with lung-only metastases, good prognostic features, and good performance status. 37 Although similar data are not available for patients who are candidates for highdose IL-2 (see later discussion), data from the UCLA renal cancer database and from a variety of publications by other groups suggest that nephrectomy also provides benefit to patients who undergo other forms of immunotherapy. 38 As for the role of nephrectomy for patients presenting with metastatic disease and considered for targeted therapies (detailed later), randomized trials are ongoing.…”
Section: Primary Treatment Of Advanced or Stage IV Diseasementioning
confidence: 99%
“…Patients most likely to benefit from cytoreductive nephrectomy before systemic therapy are those with lung-only metastases, good prognostic features, and good performance status. 37 Although similar data are not available for patients who are candidates for highdose IL-2 (see later discussion), data from the UCLA renal cancer database and from a variety of publications by other groups suggest that nephrectomy also provides benefit to patients who undergo other forms of immunotherapy. 38 As for the role of nephrectomy for patients presenting with metastatic disease and considered for targeted therapies (detailed later), randomized trials are ongoing.…”
Section: Primary Treatment Of Advanced or Stage IV Diseasementioning
confidence: 99%
“…These parameters should be taken into consideration before embarking on CRN [30]. A study conducted by the MD Anderson group has also examined who will benefit from CRN and concluded that survival differences between CRN and non-CRN patients did not begin to diverge until 8.5 months [31]. There are statistical models available in predicting the OS in patients with mRCC treated with TT, and maybe, one can make use of these models while selecting patients for CRN [32].…”
Section: Discussionmentioning
confidence: 99%
“…Appropriately selected patients for CN include: patients with a primary tumour amenable to surgical extirpation, a low risk of perioperative morbidity, good performance status (Eastern Cooperative Oncology Group [ECOG] 0 or 1), no evidence of active brain metastases, and a low number of MD Anderson risk factors (elevated lactate dehydrogenase [LDH], low albumin, symptomatic metastases, sites of disease, and clinical ≥T3 primary tumour), and less than four IMDC adverse risk features. 73,80 Moreover, there should be a low risk of rapid disease progression that would not be compatible with the delay of systemic therapy required for recovery from surgery (e.g., no high-grade or sarcomatoid features). 81 In patients who do not undergo upfront CN, but have a good response to VEGFr TKI or targeted therapy, limited metastatic disease, and good performance status, it is reasonable that CN be considered during the course of their treatment.…”
Section: Reaume Et Al Bocytosis)mentioning
confidence: 99%